Medical assistance as a decision-taking process. Pedagogical implications for the formation of the treatment hability - Luis Alberto Corona Martínez (Medisur)
This article has as objective to base the narrow relationship that settles down among the activity of taking of decisions and the doctor's basically curative assistance activity. In a general way, the exhibition of the elements is guided to the recognition of the taking of decisions, like an implicit feature in the way of the doctor's professional performance, in her/his curative assistance function, that which has important implications in the formation of the treatment ability.